Clinical diagnosis of acute coronary syndrome in patients with chest pain and a normal or non-diagnostic electrocardiogram. Issue 12 (24th November 2009) - Goodacre, S; Pett, P; Arnold, J; Chawla, A; Hollingsworth, J; Roe, D; Crowder, S; Mann, C; Pitcher, D; Brett, C
Abstract : Background: Clinical features may be used to determine which patients with suspected acute coronary syndrome (ACS), but a normal or non-diagnostic ECG, should be selected for further investigation or inpatient care. We aimed to measure the diagnostic value of clinical features for ACS. Methods: Standardised data relating to presenting characteristics, associated features and risk factors were collected at seven chest pain units established for the ESCAPE trial. All patients received troponin measurement at least 6 h after last significant symptoms, creatine kinase MB(mass) gradient over 2 h and, if appropriate, treadmill exercise testing. The reference standard of ACS was defined as troponin >0.03 ng/ml, creatine kinase MB(mass) gradient >3.0 ng/ml or early positive treadmill exercise test. Results: 1576 patients were analysed, including 132 (8.4%) with ACS. Patients with ACS were older, had longer symptom duration, were more likely to be a man, hypertensive and an ex-smoker or have pain radiating to their right arm. On multivariate analysis, only age, duration, sex and radiation of pain to the right arm were independently associated with ACS. Likelihood ratios (95% CI) were radiation of pain to the right arm, 2.9 (95% CI 1.4 to 6.3), male sex 1.2 (95% CI 1.0 to 1.3) and female sex 0.79 (95% CI 0.62 to 1.0). The area under the receiver operator characteristic curve for age was 0.629 (95% CI 0.573 to 0.686) and for duration was 0.546 (95% CI 0.481 to 0.610). Conclusion: Clinical features have very limited value for diagnosing ACS in patients with a normal or non-diagnostic ECG. Radiation of pain to the right arm increases the likelihood of ACS.